1994
DOI: 10.1139/b94-186
|View full text |Cite
|
Sign up to set email alerts
|

Water stress preconditioning of black spruce seedlings from lowland and upland sites

Abstract: 1994. Water stress preconditioning of black spruce seedlings from lowland and upland sites. Can. J. Bot. 72: 1511 -1518.One-year-old seedlings from two pairs of upland-lowland populations were subjected to three cycles of drought preconditioning. During a subsequent fourth cycle, preconditioned seedlings and seedlings that had been maintained under wellwatered conditions were subjected to a final soil drought. During the drought periods, small but significant differences in gas exchanges and water relations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 21 publications
0
10
0
4
Order By: Relevance
“…Of course, other physiological mechanisms may be involved in the trees' acclimation to drought as well. Zine E1 Abidine et al (1994) found that drought preconditioning enabled seedlings of Picea mariana (Mill.) BSP to maintain a substantially higher level of stomatal conductance and photosynthesis during a severe water stress as compared to unconditioned seedlings, but this eect was not accompanied by any changes in the concentration of osmotically active solutes.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, other physiological mechanisms may be involved in the trees' acclimation to drought as well. Zine E1 Abidine et al (1994) found that drought preconditioning enabled seedlings of Picea mariana (Mill.) BSP to maintain a substantially higher level of stomatal conductance and photosynthesis during a severe water stress as compared to unconditioned seedlings, but this eect was not accompanied by any changes in the concentration of osmotically active solutes.…”
Section: Discussionmentioning
confidence: 99%
“…Drier upland soils often exhibit a root-restricting clay horizon near the surface that perches the water table during wet periods of the year, leading to seasonal cycles of moisture surplus and deficit (Krestov et al 2000). Upland trees often appear more robust than their wetland counterparts; however, improved edaphic conditions do not seem to result in ecotypic variation in black spruce morphological features or water relations (Parker et al 1983;Zine El Abidine et al 1994). Results from greenhouse and field experiments with Norway spruce (Picea abies (L.) Karst.)…”
Section: Introductionmentioning
confidence: 99%
“…Different irrigation regimes at nursery stage are commonly used to modify eucalypt seedlings quality through short-and long-term physiological and morphological changes that might allow plants to overcome stress conditions during establishment (Zine El Abidine et al 1994;Guarnaschelli et al 2003). Manipulation of nursery environment can also alter plant chemical composition, particularly its essential oil.…”
Section: Essential Oil Quantitative Analysismentioning
confidence: 99%